2003
DOI: 10.1080/0144619032000174521
|View full text |Cite
|
Sign up to set email alerts
|

Leadership style and power relations in quantity surveying in Hong Kong

Abstract: The realization of construction projects brings together a diversity of individuals and organizations, variously forged into groups and teams, in which power is important in shaping leader/follower behaviour. Quantity surveyors, being primarily project cost consultants and procurement/contractual advisers, are employed both by the clients' and the contractors' organizations. This paper investigates aspects of leadership style and power within quantity surveying in both clients' and contractors' project 'teams'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…That is, job satisfaction has been found to have a mediating influence on the relationships between work group identification and the two forms of organisational commitment. In the construction industry, quantity surveyors in different hierarchy positions are assigned to work in groups to provide cost and contractual expertise for construction projects (Choi, 2006;Fellows, Liu and Cheung, 2003;Potts, 2008). With the work group arrangement, cooperation and collaborative working relationships are common in quantity surveyors' daily working practices (Choi, 2006), which would impose positive feelings on the quantity surveyors and would also improve their intention to stay in the organisation.…”
Section: Discussion Of Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, job satisfaction has been found to have a mediating influence on the relationships between work group identification and the two forms of organisational commitment. In the construction industry, quantity surveyors in different hierarchy positions are assigned to work in groups to provide cost and contractual expertise for construction projects (Choi, 2006;Fellows, Liu and Cheung, 2003;Potts, 2008). With the work group arrangement, cooperation and collaborative working relationships are common in quantity surveyors' daily working practices (Choi, 2006), which would impose positive feelings on the quantity surveyors and would also improve their intention to stay in the organisation.…”
Section: Discussion Of Research Findingsmentioning
confidence: 99%
“…Within quantity surveying firms, quantity surveyors in different hierarchy positions are assigned to work groups to provide cost and contractual expertise for construction projects (Choi, 2006;Fellows, Liu and Cheung, 2003;Potts, 2008). Project tasks are divided among quantity surveyors within the work group.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…However, Fellows et al (2003) found that, in Hong Kong, relationship orientation of project quantity surveyors is stronger among contractors than consultants.…”
Section: Tests Of Hypotheses H2a B C and Dmentioning
confidence: 96%
“…For example, Fellows et al (2003) studied the cultural orientation of leaders in Hong Kong and found that Chinese culture continues to have a profound influence on local culture despite over a century of British rule. Sillars and Kangari (2004) highlight the importance of cultural match between partners in the internal working of joint ventures.…”
Section: Research Rationalementioning
confidence: 99%